2014
DOI: 10.1136/bcr-2013-203442
|View full text |Cite
|
Sign up to set email alerts
|

Acute Marchiafava-Bignami disease: clinical and serial MRI correlation

Abstract: SUMMARYMarchiafava-Bignami disease (MBD) is a form of toxic demyelinating disease more often seen in chronic alcoholics. The disease process typically involves the corpus callosum and clinically often presents with altered sensorium, neurocognitive defects or seizures with acute cases often deteriorating to comatose state. The death rate is high. We report a rare case of MBD with complete clinical recovery. A 50-year-old male patient presented in an unconscious state and underwent MRI of the brain which showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
0
10
0
4
Order By: Relevance
“…Marchiafava–Bignami disease (MBD) is a toxic, demyelinating, and necrotic central nervous system disorder associated with chronic alcoholism that occasionally occurs in the patients who are not alcoholics but chronically malnourished. [ 1 , 2 ] Deficiency of group B vitamins might be the etiology of MBD; it is reported that many patients recover after treatment with B vitamins; however, others do not recover. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Marchiafava–Bignami disease (MBD) is a toxic, demyelinating, and necrotic central nervous system disorder associated with chronic alcoholism that occasionally occurs in the patients who are not alcoholics but chronically malnourished. [ 1 , 2 ] Deficiency of group B vitamins might be the etiology of MBD; it is reported that many patients recover after treatment with B vitamins; however, others do not recover. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…Экстрапонтинный ΠΌΠΈΠ΅Π»ΠΈΠ½ΠΎΠ»ΠΈΠ· характСризуСтся Π΄Π΅ΠΌΠΈΠ΅Π»ΠΈ-Π½ΠΈΠ·Π°Ρ†ΠΈΠ΅ΠΉ ΠΈ Π½Π΅ΠΊΡ€ΠΎΠ·ΠΎΠΌ мозолистого Ρ‚Π΅Π»Π° ΠΈ Π±Π΅Π»ΠΎΠ³ΠΎ вСщСства ΠΏΠΎΠ»ΡƒΡˆΠ°Ρ€ΠΈΠΉ [13,14]. ΠŸΡ€ΠΈΡ‡ΠΈΠ½ΠΎΠΉ развития Π΄Π°Π½Π½ΠΎΠ³ΠΎ состояния Π½Π°Π·Ρ‹Π²Π°ΡŽΡ‚ нСдостаток комплСкса Π²ΠΈΡ‚Π°ΠΌΠΈΠ½ΠΎΠ² Π³Ρ€ΡƒΠΏΠΏΡ‹ Π’ [13].…”
unclassified
“…Экстрапонтинный ΠΌΠΈΠ΅Π»ΠΈΠ½ΠΎΠ»ΠΈΠ· характСризуСтся Π΄Π΅ΠΌΠΈΠ΅Π»ΠΈ-Π½ΠΈΠ·Π°Ρ†ΠΈΠ΅ΠΉ ΠΈ Π½Π΅ΠΊΡ€ΠΎΠ·ΠΎΠΌ мозолистого Ρ‚Π΅Π»Π° ΠΈ Π±Π΅Π»ΠΎΠ³ΠΎ вСщСства ΠΏΠΎΠ»ΡƒΡˆΠ°Ρ€ΠΈΠΉ [13,14]. ΠŸΡ€ΠΈΡ‡ΠΈΠ½ΠΎΠΉ развития Π΄Π°Π½Π½ΠΎΠ³ΠΎ состояния Π½Π°Π·Ρ‹Π²Π°ΡŽΡ‚ нСдостаток комплСкса Π²ΠΈΡ‚Π°ΠΌΠΈΠ½ΠΎΠ² Π³Ρ€ΡƒΠΏΠΏΡ‹ Π’ [13]. ΠšΠ»ΠΈΠ½ΠΈΡ‡Π΅ΡΠΊΠ°Ρ ΠΊΠ°Ρ€Ρ‚ΠΈΠ½Π° Π‘ΠœΠ‘ складываСтся ΠΈΠ· психичСских Π½Π°Ρ€ΡƒΡˆΠ΅Π½ΠΈΠΉ, измСнСния личности, Π³Π°Π»Π»ΡŽΡ†ΠΈΠ½Π°Ρ†ΠΈΠΉ, сниТСния ΠΈΠ½Ρ‚Π΅Π»Π»Π΅ΠΊΡ‚Π° Π²ΠΏΠ»ΠΎΡ‚ΡŒ Π΄ΠΎ Π΄Π΅ΠΌΠ΅Π½Ρ†ΠΈΠΈ, Π΄ΠΈΠ·Π°Ρ€Ρ‚Ρ€ΠΈΠΈ, ΠΏΠΈΡ€Π°ΠΌΠΈΠ΄Π½ΠΎΠ³ΠΎ синдрома, Π½Π°Ρ€ΡƒΡˆΠ΅Π½ΠΈΡ равновСсия, эпилСптичСских ΠΏΡ€ΠΈ-ступов, симптомов ΠΌΠ΅ΠΆΠΏΠΎΠ»ΡƒΡˆΠ°Ρ€Π½ΠΎΠ³ΠΎ разобщСния, ΠΈΠ·ΠΌΠ΅Π½Π΅-ния сознания Π²ΠΏΠ»ΠΎΡ‚ΡŒ Π΄ΠΎ ΠΊΠΎΠΌΡ‹ ΠΈ, Π² ΠΊΠΎΠ½Π΅Ρ‡Π½ΠΎΠΌ счСтС, Π³ΠΈΠ±Π΅Π»ΠΈ больного.…”
unclassified
See 2 more Smart Citations